PERTUMBUHAN EKONOMI MEMODERASI HUBUNGAN PENDAPATAN DAERAH DAN DANA ALOKASI TERHADAP BELANJA MODAL - Lilis Setyowati (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2023)
This study aims to determine the effect of regional original income, general allocation funds, and special allocation funds on capital expenditures with economic growth as a moderating variable in Central Java Province for the 2019 - 2021 period. Capital expenditure is a regional budget expenditure used to purchase assets or develop assets. whose useful life is more than one accounting period. The analytical method in this study is Moderated Regression Analysis (MRA) using data from 2019 - 2021. The analytical techniques used are statistical tests, classical assumption tests, coefficients of determination, and moderate regression analysis. The results of the study show that local revenue and general allocation funds have an effect on capital expenditures, while special allocation funds have no effect on capital expenditures. Economic growth can moderate the effect of general allocation funds and special allocation funds on capital expenditures, while economic growth cannot moderate the effect of local revenue on capital expenditures.